Optimization of the Role and Function of Head Nurse Management in the Handover Process Between Shifts - Endah Ratna Samapty Winarsih; Tuti Afriani; Andi Amalia Wildani; Tenti Ariyanti (Indonesian Journal of Global Health Research, 2026)
The inter-shift handover is a critical process that significantly impacts patient safety. Communication failures during handover are identified as a major cause of safety incidents. In a referral hospital in Jakarta, the managerial role in handover remains suboptimal, indicated by inconsistent supervision and lack of standard practice. To optimize the role and function of nursing management in the handover process to enhance communication and patient safety. This case report employed a descriptive qualitative approach. Data were collected through interviews, observations, and questionnaires involving staff nurses in the GP2 inpatient unit. Interventions included the development of a standardized operating procedure (SOP) for shift handovers, simulation of bedside handovers using the SBAR format, and strengthened head nurse supervision through structured monitoring. The intervention improved understanding and acceptance of the SOP (100% of respondents found it understandable and logical) and enhanced communication quality (83–87% of respondents reported information was complete, accurate, and interactive). Head nurse supervision was perceived as strong (over 90%). However, only 33.3% consistently performed bedside handovers, and documentation in the electronic medical record (EMR) system was not optimal. Key challenges included time constraints, workload, and the lack of integrated documentation systems. The application of Kotter's change model contributed to the success of the intervention by establishing a sense of urgency, forming a guiding coalition, and reinforcing the role of management as change agents. Optimizing managerial functions has proven effective in improving communication and patient safety. Continued monitoring of bedside handover practices and sustained clinical supervision are recommended to maintain the quality of nursing services.